The practices of financial governance in Malaysian accountant general's department, Putrajaya : an analysis from the perspectives of Maqasid Shariah / Fatin Norshahira Mohd Razid - Mohd Razid, Fatin Norshahira (2018)
Financial Governance that expose to help in their knowlegde to improve their standard of life. It develop an awareness of industrial approach to problem solving, based on broad understanding of process and mode of operation of organization. The purpose of the study is to know the financial governance management through the method or element that have been used. This research is done at Accountant General's Department of Malaysia, Putrajaya that I was stated in industrial training for 4 month. The oucome of this research shows that the financial governance management have a good method and elements in its activities through prepare on Budget 2019, management of budget in accounting anf financing, supply expenses, liability expenses and development expenses. This research shows that the Accountant General is one of main roles that responsibility to manage and ensure that the financial governance at Accountant General's Department of Malaysia in good and excellent management to gain profit every year. Besides that, the Accountant General's Department of Malaysia have being establish the Badan Kebajikan Perkhidmatan Akauntan Negara Malaysia to all officers under JANM and Accounting Office to their welfare society in better life for them. Therefore, the financial governance management have good impact to expand the Malaysia's economy that relate financing and accounting properly without have deficit impact on government.